Occlusion of two semicircular canals does not disrupt normal hearing in adult mice - Wang, Tianying; Liu, Huizhan; He, David Z.; Li, Yi (Frontiers in Neurology, 2022)
Vertigo is a debilitating disease affecting 15% - 20% of adults worldwide. Vestibular peripheral vertigo is the most common cause of vertigo, often due to Meniere’s disease and benign paroxysmal positional vertigo. Although some vertigo symptoms can be controlled by conservative treatment and/or vestibular rehabilitation therapy, these treatments do not work for some patients. Semicircular canal occlusion surgery has proven to be very effective for these patients with intractable vertigo. However, its application is limited due to concern that the procedure will disrupt normal hearing. In this study, we investigated if occlusion of two semicircular canals would jeopardize auditory function by comparing auditory function and hair cell morphology between the surgical and contralateral ears before and after the surgery in a mouse model. By measuring the auditory brainstem response and distortion product otoacoustic emission four weeks post-surgery, we show that auditory function does not significantly change between the surgical and contralateral ears. In addition, confocal imaging has shown no hair cell loss in the cochlear and vestibular sensory epithelia, and scanning electron microscopy also indicates normal stereocilia morphology in the surgical ear. More importantly, the endocochlear potential measured from the surgical ear is not significantly different than that seen in the contralateral ear. Our study suggests that occlusion of two semicircular canals does not disrupt normal hearing in the mouse model, providing a basis to extend the procedure to patients, even those with normal hearing, benefitting more patients with intractable vertigo attacks.